Proportionality and the rule of law : rights, justification, reasoning - Huscroft, Grant, Ed (New York University Press, 2014)
"To speak of human rights is to speak of proportionality. It is no exaggeration to claim that proportionality has overtaken rights as the orienting idea in contemporary human rights law and scholarship. Proportionality has been received into the constitutional doctrine of courts in continental Europe, the United Kingdom, Canada, New Zealand, Israel, and South Africa, as well as the jurisprudence of treaty-based legal systems like the European Court of Human Rights, giving rise to claims of a global model, a received approach, or, simply, the best-practice standard of rights adjudication. Even in the United States, which is widely understood to have formally rejected proportionality, some argue that the various levels of scrutiny adopted by the US Supreme Court are analogous to the standard questions posed by proportionality. As proportionality scholars are well aware, some of the early literature on balancing and rights is American, with special reference to the First Amendment. Notwithstanding proportionality's popularity, there is no consensus on its methodology. Much less does the use of a proportionality doctrine guarantee consensus on substantive rights questions. What the principle of proportionality promises is a common analytical framework, a framework the significance of which is not in its ubiquity (a mere fact), but because its structure influences (some would say controls) how courts reason to conclusions in many of the great moral and political questions confronting political communities. As a framework, proportionality analysis is superficially straightforward, setting out four questions in evaluating whether the limitation of a right is justifiable. A serviceable - but by no means canonical"--